Crack Group Effect Analysis of the Stress-Release Boot of Solid Rocket Motor Based on Numerical Simulation. (30th November 2021) - Li, Tianpeng; Han, Junli; He, Yong; Guo, Yu
Abstract : Due to the complex process of the insulation layer patch in solid rocket motor (SRM), only manual patch could be used. Sometimes weak bonding or debonding in each joint surface was inevitable. This study is aimed at determining the crack group effect of insulation and interfacial debonded crack in the wide-temperature SRM. The crack group appeared in the front area of the ahead stress-release boot and was induced by low temperature, axial overload, or interface bonding failure. Based on the viscoelastic finite element method, singular crack elements and singular interfacial crack elements at the tips of crack group were established to calculate J -integral. Varying according to the length and position of cracks, the J -integral of crack tips was, respectively, calculated to prejudge their stability and the crack group effect. The results showed that collinear crack group appeared in the front stress-release boot layer, and the crack group had a certain shielding effect on the main crack when the SRM was launched at low temperature. When noncollinear crack group appeared in the front stress-release boot layer, the crack group effect changed with the length of the main crack. The crack group first had a shielding effect on the main crack and then had a strong strengthening effect. The experimental test of the simulated specimen revealed that numerical simulation results matched the experimental test results.